Public Reason Liberalism and Sex‐Neutral Marriage A Response to Francis J. Beckwith. (14th September 2015) - Walker, Greg
Abstract: This article responds to an article by Francis J. Beckwith that argued that the consistent application of generic liberal principles requires that same‐sex marriage not be recognised in civil law. This response demonstrates that Beckwith's article contains a series of interpretative and substantive flaws that render his argument unsuccessful. These relate to a misinterpretation of core liberal principles and a sidestepping of the matter of undue bias against same‐sex partners. In correcting these flaws I tentatively propose a Voltairean argument in favour of same‐sex civil marriage for those citizens with moral qualms about same‐sex relationships derived from their reasonable comprehensive doctrine.